A QUESTÃO DA MEMÓRIA NO ARQUIVO PESSOAL DE SANTOS DUMONT - Bárbara Cristina Barbosa Pinto da Silva (TRF2, 2020)
This paper aims to discuss the issues surrounding memory, based on the Personal Archive of Santos Dumont. The intention is to bring up some discussions that took place in the classroom, during the discipline Archive, Memory and Heritage, a course taken in the Post-Graduate Program in Management of Documents and Archives based on some of the texts read. The focus will be to discuss issues related to memory, based on the collection of the father of aviation.